Peran Teknologi dalam Meningkatkan Efisiensi Pertanian - Julvin Saputri Mendrofa; Martirah Warni Zendrato; Nisiyari Halawa; Elias Elwin Zalukhu; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Abstracts. This research examines the role of genetic technologies in the conservation of threatened marine species with a focus on the effectiveness of methods and the successful application of advanced techniques. The background of this research is driven by the biodiversity crisis affecting marine species, which requires innovative approaches for protection and recovery. The main objective of the study was to evaluate various genetic methods in improving the conservation of threatened species and determine their success in practice. The methods used included an in-depth literature review of genetic techniques, case studies of field applications, and analysis of results obtained from various sources. Findings suggest that genetic methods, such as CRISPR and DNA barcoding techniques, have significant potential to improve the effectiveness of marine species conservation by providing solutions to specific problems related to threatened species. Implications of this research include recommendations for the application of genetic techniques in conservation programs as well as encouragement for further research to address complex conservation challenges. This research contributes to the development of more effective genetics-based conservation strategies, offering practical guidance for future policies and actions.